PENYULUHAN KESEHATAN TENTANG PENTINGNYA PEMBERIAN KAPSUL VITAMIN A PADA BALITA - Indah Mastikana; Risma Ikha Paramitha (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2022)
The purpose of this health education activity is to increase knowledge, attitudes, and behavior about the importance of giving vitamin A capsules to toddlers in order to prevent vitamin A deficiency. The Community Service method used in the activity is to socialize in the form of counseling about the importance of giving vitamin A capsules to toddlers. . Participants in the health education activities were 18 mothers of children under five. After the health education activity was carried out, an evaluation was carried out with the results that the participants who attended were able to know and understand the material presented, it was proven that the participants were enthusiastic about asking about the importance of giving vitamin A capsules to toddlers. The result of this health education activity is an increase in the level of knowledge, behavior and enthusiasm of mothers or participants by participating in health education activities about the importance of giving vitamin A capsules to toddlers. This can be seen from the results of the post test that has been carried out, the results are that participants who have a good level of knowledge are fourteen of the eighteen participants. Keywords: Knowledege, Attitude, Behavior, vitamin A, toodler